PowerPlay: Adaptation of game-based learning on empowering energy conservation - Zulkifli, Zuhri Arafah; Halim, Faiqah Hafidzah; Johari, Nur Farahin Mohd; Zaini, Hazrati; Mangshor, Nur Nabilah Abu; Ishak, Norshahidatul Hasana; Samah, Khyrina Airin Fariza Abu; Faisal, Muhammad Alif Mohd (2024)
PowerPlay is a game-based learning tool to educate children about energy conservation. It addresses the gap in effective mediums for teaching energy conservation to young learners and the limitations of traditional methods. This study employs the waterfall model methodology to design and implement an interactive educational game. This adaptation features two game modes, EcoFact and EcoGuess, which incorporate educational videos and enjoyment factors to engage children in fun learning about environmental responsibility. This study conducted enjoyment testing following the guidelines from eGameFlow to ensure an engaging and motivating learning experience. Results demonstrate high user engagement and enjoyment levels, validating the game’s educational impact. PowerPlay emerges as a promising tool for fostering environmental awareness and responsibility in children through an innovative and enjoyable medium.